Perancangan Sistem Informasi Marketplace "Danzu Store" Berbasis Web untuk Efisiensi Layanan Pelanggan - Irwansyah, Irwansyah; Paramita, Bella; Davizan, Serry; Aljibran, M. Irdan (Jurnal Bisnis Digital & Perbankan, 2025)
A marketplace is an online buying and selling platform that facilitates consumers in conducting transactions without having to visit the store directly. This study aims to design and implement the "Danzu Store" marketplace information system from the user’s perspective, focusing on the sale of daily necessities. The system is intended to simplify users in searching for and purchasing retail products such as food, beverages, toiletries, and another household needs online. The system development methodology uses the waterfall approach with stages including requirement analysis, system design, implementation, and testing. The technologies employed are PHP or Hypertext Preprocessor, as the programming language, MySQL as the database, and Bootstrap for the user interface. The main features of the system include product listings, shopping cart, payment methods, order history, and user login. The implementation results show that the system functions properly and provides ease of transaction for users.